2002
DOI: 10.1074/jbc.m206369200
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin T Variants Produced by Aberrant Splicing of Multiple Exons in Animals with High Instances of Dilated Cardiomyopathy

Abstract: Adult cardiac muscle normally expresses a single cardiac troponin T (cTnT). As a potential pathogenic mechanism for turkey dilated cardiomyopathy, the splice-out of a normally constitutive exon generates an additional low molecular weight cTnT with altered conformation and function. We further found that aberrant splicing of cTnT also occurs in several mammals correlating to dilated cardiomyopathy. Skipping of the same exon as that in the turkey was found in the canine cTnT. Spliceout of the adjacent exon 6 oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 42 publications
(62 reference statements)
3
101
0
1
Order By: Relevance
“…Transgenic expression of Tnnt3 in the heart negatively affects heart function in line with the degree of troponin complex heterogeneity causing dilation in aged mouse hearts (33). Moreover, a splice variant of cardiac TnT that resembles Tnnt3 causes DCM in multiple animal models (34) and is expressed in failing human hearts (35). Overexpression of the fast-twitch Myl1 gene also alters the contractile function of the heart (36) and is up-regulated exclusively in patients with DCM (37).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic expression of Tnnt3 in the heart negatively affects heart function in line with the degree of troponin complex heterogeneity causing dilation in aged mouse hearts (33). Moreover, a splice variant of cardiac TnT that resembles Tnnt3 causes DCM in multiple animal models (34) and is expressed in failing human hearts (35). Overexpression of the fast-twitch Myl1 gene also alters the contractile function of the heart (36) and is up-regulated exclusively in patients with DCM (37).…”
Section: Discussionmentioning
confidence: 99%
“…The cTnI-R111C mutation, together with aberrantly spliced cardiac TnT, which causes dilated cardiomyopathy, is present in wild turkey hearts (2,3). We recently demonstrated that cTnI-K118C and the aberrantly spliced cardiac TnT mutually canceled each other's dominantly negative effects when they were coexpressed in the hearts of double-transgenic mice (27).…”
mentioning
confidence: 99%
“…With these modifications, they were able to resolve alpha-and beta-MHC that differ by only 0.4 kDa. Similarly, Biesiadecki et al [76] used a 14% gel with an acrylamide:bisacrylamide ratio of 200:1 to resolve TnT isoforms that differ by as little as three amino acid residues. In order to separate titin isoforms, which can have an MW up to 4 MDa, Warren et al [70,77] developed a vertical SDS-agarose gel system to resolve huge proteins.…”
Section: Shifts In Isoform Populationsmentioning
confidence: 99%
“…Compared to SDS-PAGE gels, SDSagarose gels offer improved resolution of titin isoforms, and higher transfer efficiency for subsequent analysis by Western blot. In addition to 1-DE, 2-DE were also used to separate similar isoforms of myofilament proteins, such as atrial light chain [67] and TnT [76]. Another way to differentiate closely migrating isoforms is to use isoform-specific antibodies.…”
Section: Shifts In Isoform Populationsmentioning
confidence: 99%